Rancang Bangun Aplikasi Pengendalian Persediaan Bahan Baku Berbasis Website Menggunakan Metode Safety Stock dengan Perhitungan Service Level pada CV Dwi Teknik - Sayang, Ega Syahputra; Setyawan, Henry Bambang; Lemantara, Julianto (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2022)
CV Dwi Teknik is a spring manufacturer company located on jl. Balong Dinding Gg 3, Menganti, Gresik. The problem in this company is that the recording transaction of stock materials still uses notes to record transactions. This can pose a risk of delays in reporting or recording stock transaction of materials due to the absence of real time recording of transaction of stock materials. There is no safety stock in this company where safety stock is needed so that there is a stock of materials available when there is high demand. Based on these problems, the solution is by making a application that can record transaction of stock materials and safety stock calculator using service level calculation. Based on the test results and evaluation, it can be concluded that this application can record a transaction of stock materials, perform safety stock using service level calculations, a notification that displays materials that have reached safety stock, create a reports of transaction of stock materials or reports of safety stock.